PVC material, its preparation method and application

The modified graphene mixture was prepared by ball milling, which solved the problems of uneven dispersion and poor compatibility of graphene in PVC composites, improved the mechanical properties and low-temperature impact resistance of PVC materials, and achieved uniform dispersion and good compatibility of graphene in PVC.

CN117866352BActive Publication Date: 2026-11-03福建联塑新材料科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311872125.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-29
Publication Date
2026-11-03
Estimated Expiration
2043-12-29

AI Technical Summary

Technical Problem

The mechanical properties of existing graphene-reinforced rigid PVC composites still need to be further improved. Graphene is unevenly dispersed in PVC composites and has poor compatibility with PVC, making it difficult to fully demonstrate its excellent performance.

Method used

A modified graphene mixture was prepared by ball milling using graphite powder, plasticizer, and quaternary ammonium salt surface treatment agent. The ball milling process was used to exfoliate graphite and modify the surface of graphene to improve its dispersibility and compatibility in PVC. The plasticizer was inserted into the PVC molecular chain to reduce entanglement, and the quaternary ammonium salt treatment agent improved the interfacial compatibility between graphene and PVC.

Benefits of technology

It significantly improves the mechanical properties of PVC materials, especially hydraulic properties and low-temperature impact properties, achieves uniform dispersion and good compatibility of graphene in PVC, and enhances the overall performance of PVC composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117866352B_ABST
    Figure CN117866352B_ABST
Patent Text Reader

Abstract

The application discloses PVC material and a preparation method and application thereof. The PVC material comprises the following components in parts by weight: 100 parts of PVC resin; 1-5 parts of modified graphene mixture; 5-15 parts of filler; 1-5 parts of processing aid; 3-5 parts of stabilizer; and 0.3-1.1 parts of lubricant. The modified graphene mixture is a mixture obtained by ball milling of graphite powder, a plasticizer and a quaternary ammonium salt surface treatment agent. The PVC material has good dispersibility of graphene, and the PVC pipe prepared from the PVC material has no damage in impact test performance, and has no damage and no leakage in hydraulic performance test under 40 MPa for 1 hour, and has good impact resistance and hydraulic performance, so that the PVC material can meet the use requirement and can be widely applied to preparation of hard PVC pipes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, and more specifically, to a PVC material, its preparation method, and its application. Background Technology

[0002] In the manufacturing process of PVC-U pipes, improvements in their physical and chemical properties, such as strength, impact resistance, and thermal stability, are mainly achieved through modifications to composite materials and processing techniques. Nanotechnology is a primary method for modifying PVC composite materials. Graphene, a nanomaterial, possesses superior mechanical and electrical properties, and its application in the manufacturing process of PVC-U pipes will effectively enhance the performance of the PVC-U material.

[0003] Currently, there are three main methods for applying graphene in PVC composites: in-situ polymerization, solution blending, and melt blending. In the PVC pipe manufacturing process, the first two methods have high requirements for cost, technology, and equipment, making large-scale application impossible. Melt blending is the simplest and most convenient method. However, due to graphene's unique structure, it tends to agglomerate due to strong interparticle adsorption forces, making it difficult to disperse evenly in PVC composites. Furthermore, graphene is a non-polar material, resulting in poor interfacial compatibility with PVC, thus hindering the full realization of its superior properties.

[0004] The prior art discloses a graphene-reinforced rigid PVC thermally conductive composite material, comprising polyvinyl chloride resin, graphene, graphene surface treatment agent, thermally conductive filler, steric hindrance filler, processing aid, stabilizer, plasticizer, toughening agent, antioxidant, and other additives, including lubricating dispersants. However, this prior art has not tested the relevant properties of PVC pipes, and its tensile strength is only up to 40.6 MPa, indicating that its mechanical properties need further improvement. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of existing graphene-reinforced rigid PVC composite materials whose mechanical properties still need to be further improved. The present invention provides a PVC material comprising a mixture obtained by ball milling graphite powder, plasticizer and quaternary ammonium salt surface treatment agent, which is beneficial to improving the dispersibility of graphene and the compatibility between graphene and PVC, thereby improving the mechanical properties of PVC material.

[0006] Another object of the present invention is to provide a method for preparing PVC material.

[0007] Another object of the present invention is to provide an application of PVC material in the preparation of PVC pipes.

[0008] The above-mentioned objective of this invention is achieved through the following technical solution:

[0009] A PVC material, by weight, comprises the following components:

[0010]

[0011] The modified graphene mixture is a mixture obtained by ball milling graphite powder, plasticizer, and quaternary ammonium salt surface treatment agent.

[0012] The quaternary ammonium salt surface treatment agent has the formula R3R'N+X-, wherein:

[0013] -R stands for methyl;

[0014] -R' belongs to the group consisting of the following groups: hydrogen, C12-C18 alkyl, or epoxy;

[0015] -X- represents the anions of chlorine, bromine, iodine, and fluorine;

[0016] The ball milling temperature is 65-90℃, the ball milling time is 20-30h, and the ball milling speed is 800-1000rpm / min;

[0017] The weight ratio of plasticizer, quaternary ammonium salt surface treatment agent and graphite powder is (1-2):(0.4-0.8):1.

[0018] This invention improves the dispersibility of graphene in PVC materials and its compatibility with PVC through the synergistic effect of its components, thereby improving the mechanical properties of PVC materials, especially significantly improving the hydraulic performance and low-temperature impact performance of PVC.

[0019] The underlying principle may be as follows: Graphite is dispersed in a plasticizer, and the high-speed shearing of ball milling is used to rapidly and efficiently exfoliate the graphite, resulting in a stable dispersion of few-layer graphene. After the graphite is exfoliated, a quaternary ammonium salt surface treatment agent modifies the graphene surface through covalent bonding, i.e., electron migration (between the graphene and the ammonium salt portion). This reduces the re-agglomeration of the exfoliated few-layer graphene, increases its dispersibility, and, after surface modification, the organic portion of the quaternary ammonium salt surface treatment agent exhibits good compatibility with PVC materials, resulting in better conductivity under stress in the PVC composite material, thereby improving the overall performance of the PVC composite material.

[0020] Plasticizers have good compatibility with polyvinyl chloride (PVC) resin. When plasticizers and PVC resin melt, the small-molecule plasticizers are inserted into the PVC molecular chains, weakening the van der Waals forces between PVC polymer molecular chains, increasing the distance between molecular chains, and reducing the entanglement between PVC molecular chains. This increases the dispersion of graphene in the PVC matrix, and the plasticizer can also improve the fluidity of PVC materials and optimize the molding process of PVC pipes.

[0021] Quaternary ammonium salt surface treatment agents can modify the surface of graphene, increase the dispersibility of graphene, and also increase the compatibility of graphene with PVC resin and plasticizer in PVC materials, thus solving the problem of graphene's tendency to agglomerate.

[0022] Modifying graphene can improve its dispersibility in polyvinyl chloride, demonstrating its excellent thermal and mechanical properties.

[0023] Preferably, the quaternary ammonium salt surface treatment agent is one or more of dodecyltrimethylammonium bromide, octadecyltrimethylammonium bromide, or glycidyltrimethylammonium chloride.

[0024] Preferably, the ball milling temperature is 70–85°C.

[0025] Preferably, the plasticizer is an aliphatic diester plasticizer.

[0026] In this invention, aliphatic diester plasticizers can not only improve the dispersibility of graphene, but also improve the low-temperature resistance of PVC materials.

[0027] More preferably, the aliphatic diester plasticizer is one or more of dioctyl adipate, dioctyl sebacate, or dibutyl sebacate.

[0028] Preferably, the filler is one or more of calcium carbonate, titanium dioxide, or pigment.

[0029] The role of nano-calcium carbonate is to reduce melt viscosity, improve processability and melt demolding properties, and reduce the formulation cost of PVC pipes.

[0030] Titanium dioxide and color powder are used to adjust the appearance color of pipes, improve their weather resistance, and extend their service life.

[0031] Preferably, the processing aid is one or more of methyl methacrylate / acrylate copolymer, methyl methacrylate / styrene copolymer, methyl methacrylate / vinyl acetate copolymer, or acrylonitrile / styrene copolymer.

[0032] The role of processing aids is to adjust melt viscosity, improve melt uniformity, and broaden the processing window.

[0033] Preferably, the lubricant is one or more of polyethylene wax, oxidized polyethylene wax, stearic acid, or monoglyceride.

[0034] The function of lubricants is to regulate the fluidity of the melt, improve processability and melt release properties, and broaden the processing range.

[0035] Preferably, the stabilizer is a calcium-zinc composite stabilizer.

[0036] In practical applications, the stabilizer of the present invention can be a stabilizer commonly used in the art, such as a calcium-zinc composite stabilizer.

[0037] The role of calcium-zinc stabilizers is to extend the decomposition time of PVC, broaden the processing range, and extend the service life of pipes.

[0038] The present invention also protects a method for preparing the PVC material described in any of the above claims, comprising the following steps: ball milling graphite powder, plasticizer and quaternary ammonium salt surface treatment agent to obtain a modified graphene mixture; mixing the modified graphene mixture with the remaining components and stirring and heating; stirring and cooling when the temperature reaches 115-125°C; and plasticizing and extruding when the temperature drops below 50°C to obtain the PVC material.

[0039] This invention first prepares a modified graphene mixture, that is, the graphene material is first dispersed in a plasticizer with a quaternary ammonium salt surface treatment agent, and then the blend is added to PVC resin. This reduces the formation of graphene agglomerates and allows it to be better dispersed between PVC molecules along with the plasticizer. The quaternary ammonium salt surface treatment agent can also improve the interfacial compatibility between graphene and polymer. In this way, the stiffening and toughening effect of graphene can be better reflected compared with direct addition, thereby improving the processing performance of PVC materials and improving the mechanical and low-temperature resistance of the products.

[0040] This invention also protects the use of any of the PVC materials described above in the preparation of PVC pipes.

[0041] This invention also protects a method for preparing PVC pipes from the PVC material described in any of the above claims, comprising the following steps: ball milling graphite powder, plasticizer, and quaternary ammonium salt surface treatment agent to obtain a modified graphene mixture; first, adding the modified graphene mixture and PVC resin into a hot mixing tank and heating and stirring to 65-85°C; then, adding other raw materials sequentially into the hot mixing tank, heating and stirring; when the temperature reaches 115-125°C, discharging the material into a cold mixing tank and stirring and cooling; stopping stirring when the temperature drops below 50°C; extruding and plasticizing, molding, and cutting to obtain rigid polyvinyl chloride pipes.

[0042] In a specific embodiment, the extrusion plasticizing machine is a conical twin-screw extruder with a barrel temperature of 160℃~185℃.

[0043] Compared with the prior art, the beneficial effects of the present invention are:

[0044] This invention discloses a PVC material comprising a mixture obtained by ball milling graphite powder, plasticizer, and quaternary ammonium salt surface treatment agent, which is beneficial to improving the dispersibility of graphene and its compatibility with PVC, thereby improving the mechanical properties of the PVC material.

[0045] The graphene in the PVC material of this invention has good dispersion. The impact test of the PVC pipe prepared from the PVC material shows no damage, and the hydraulic performance test shows no damage or leakage at 40MPa for 1 hour. It has good impact resistance and hydraulic performance, meets the application requirements, and can be widely used in the preparation of rigid PVC pipes. Attached Figure Description

[0046] Figure 1 Image of unmilled graphite using a scanning electron microscope (SEM).

[0047] Figure 2 This is a scanning electron microscope (SEM) image of the modified graphene mixture from Example 1. Detailed Implementation

[0048] The present invention will be further described below with reference to specific embodiments, but the embodiments do not limit the present invention in any way. Unless otherwise stated, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.

[0049] PVC resin, grade SG-5, from Zhongtai Chemical Co., Ltd.

[0050] Plasticizer 1, dioctyl adipate.

[0051] Quaternary ammonium salt surface treatment agent 1, dodecyltrimethylammonium bromide.

[0052] Quaternary ammonium salt surface treatment agent 2, octadecyltrimethylammonium bromide.

[0053] Quaternary ammonium salt surface treatment agent 3, glycidyltrimethylammonium chloride.

[0054] Filler: Titanium dioxide SR-2400, Shandong Dongjia Group Co., Ltd.

[0055] Filler: Nano calcium carbonate is CCR-5, Guangxi Huana New Materials Co., Ltd.

[0056] Filler: Gray pigment powder, Dongguan Chuangtexin Plastics Technology Co., Ltd., commercially available, and the same one was used in all examples and comparative examples.

[0057] The processing aid is LPA-40, manufactured by Shandong Rike Chemical Co., Ltd.

[0058] The calcium-zinc stabilizer, R618R, is commercially available from Baerroch Plastic Additives (Jiangsu) Co., Ltd., and the same stabilizer was used in all examples and comparative examples.

[0059] The lubricant, RL-100, is from Shanghai Ruile Chemical Co., Ltd., and is commercially available. The same lubricant was used in all examples and comparative examples.

[0060] Examples 1-5

[0061] A PVC material, by weight, comprises the following components:

[0062] PVC resin; modified graphene mixtures; fillers; processing aids; stabilizers and lubricants.

[0063] The filler is a mixture of nano-calcium carbonate, titanium dioxide, and pigment, wherein the weight ratio of nano-calcium carbonate, titanium dioxide, and pigment is 12:4:1.

[0064] The specific content of each component is shown in Table 1 below.

[0065] The modified graphene mixture was prepared by ball milling graphite powder, plasticizer 1 and quaternary ammonium salt surface treatment agent 1, with the weight ratio of plasticizer, quaternary ammonium salt surface treatment agent and graphite powder being 1:0.5:1.

[0066] The ball milling temperature was 80℃, the ball milling time was 24h, and the ball milling speed was 850rpm / min.

[0067] Table 1. PVC material composition of each embodiment (by weight)

[0068]

[0069]

[0070] The specific preparation method of the above-mentioned PVC material is as follows:

[0071] First, the mixture of polyvinyl chloride resin powder and modified graphene is added to a hot mixing tank, heated and stirred. When the material temperature reaches 80°C, other raw materials are added to the hot mixing tank in sequence, and the temperature is continued to rise and stir. When the temperature reaches 120°C, the material is discharged into a cold mixing tank for stirring and cooling. When the temperature drops below 50°C, stirring is stopped. The material is then extruded and plasticized using a conical twin-screw extruder at a barrel temperature of 175°C. Finally, it is molded at 185°C using a mold and cut to obtain the rigid polyvinyl chloride pipe.

[0072] Example 6

[0073] A PVC material, which differs from Example 2 in that the quaternary ammonium salt surface treatment agent in the modified graphene mixture is quaternary ammonium salt surface treatment agent 2.

[0074] The rest is the same as in Example 2, and will not be repeated here.

[0075] Example 7

[0076] A PVC material, unlike Example 2, uses quaternary ammonium salt surface treatment agent 3 in the modified graphene mixture.

[0077] The rest is the same as in Example 2, and will not be repeated here.

[0078] Example 8

[0079] A PVC material, which differs from Example 2 in that the ball milling temperature is 65°C.

[0080] The rest is the same as in Example 2, and will not be repeated here.

[0081] Example 9

[0082] A PVC material, which differs from Example 2 in that the ball milling temperature is 90°C.

[0083] The rest is the same as in Example 2, and will not be repeated here.

[0084] Comparative Example 1

[0085] A PVC material, unlike Example 2, uses dioctyl phthalate (DOP) as the plasticizer.

[0086] The rest is the same as in Example 2, and will not be repeated here.

[0087] Comparative Example 2

[0088] A PVC material, unlike Example 2, does not include quaternary ammonium salts in the modified graphene mixture.

[0089] The rest is the same as in Example 2, and will not be repeated here.

[0090] Comparative Example 3

[0091] A PVC material, unlike Example 2, in which the quaternary ammonium salt surface treatment agent is replaced with a titanate coupling agent in the modified graphene mixture.

[0092] The rest is the same as in Example 2, and will not be repeated here.

[0093] Comparative Example 4

[0094] A PVC material, which differs from Example 2 in that the ball milling temperature is 30°C.

[0095] The rest is the same as in Example 2, and will not be repeated here.

[0096] Comparative Example 5

[0097] A PVC material, unlike Example 2, does not pre-prepare a modified graphene mixture, but directly mixes the same graphite powder, plasticizer, and quaternary ammonium salt surface treatment agent as in Example 2 with PVC resin.

[0098] The rest is the same as in Example 2, and will not be repeated here.

[0099] Comparative Example 6

[0100] A PVC material, unlike Example 2, does not include the modified graphene mixture.

[0101] The rest is the same as in Example 2, and will not be repeated here.

[0102] Result detection

[0103] The PVC materials used in the above embodiments and comparative examples were used to prepare polyvinyl chloride (PVC) pipes with an outer diameter of 110 mm and a wall thickness of 4.2 mm. The PVC pipes were tested using the following performance test method: GB / T10002.1-2006, "Rigid Polyvinyl Chloride (PVC-U) Pipes for Water Supply".

[0104] The impact test results are characterized by the number of broken samples divided by the number of samples.

[0105] The hydraulic performance was tested under the following conditions: 40 MPa for 1 hour.

[0106] The specific test results are shown in Table 2 below:

[0107] Table 2

[0108]

[0109]

[0110] As can be seen from the above data, the PVC pipe prepared by the PVC material in this embodiment of the invention shows no breakage in the impact test, and the hydraulic performance test shows no breakage or leakage at 40MPa for 1 hour. It has good impact resistance and hydraulic performance, and the tensile strength is above 45MPa, reaching 45.4 to 48.8MPa. It has a low longitudinal shrinkage rate and a high Vicat softening temperature, which can meet the application requirements and can be widely used in the preparation of PVC-U pipes.

[0111] As can be seen from Example 2 and Comparative Example 1, Example 2 has excellent impact resistance. This is because in the graphene-modified mixture, the aliphatic plasticizer acts as both a graphene solvent and a cold-resistant plasticizer in PVC, reducing the brittleness of PVC in low-temperature environments.

[0112] As can be seen from Example 2, Comparative Example 2, and Comparative Example 3, Example 2 has excellent impact resistance, hydraulic performance, and tensile strength. This is because after graphite is peeled off, it forms few-layer graphene. After surface treatment, it can not only increase the distance between graphene layers and reduce re-agglomeration, but also increase its interfacial compatibility in the PVC matrix. It can efficiently transfer external tensile or impact energy and reduce the energy borne by PVC.

[0113] In Comparative Example 4, the ball milling temperature was too low, resulting in poor graphene surface treatment. The quaternary ammonium salt did not effectively adhere to the graphene surface, and its impact performance, tensile performance, and hydraulic performance could not meet the requirements.

[0114] In Comparative Example 5, the PVC pipes made from untreated graphite exhibited poor tensile strength, hydraulic performance, and impact resistance, failing to meet the requirements.

[0115] In Comparative Example 6, without the addition of graphene, plasticizer, and quaternary ammonium salt surface treatment agent, the impact and hydraulic properties did not meet the requirements of this invention, and the tensile strength was significantly worse than that of the Example.

[0116] from Figure 1 and Figure 2 It can be seen that a graphene sheet structure was formed in the modified graphene mixture of Example 1. This indicates that graphite powder was transformed into graphene.

[0117] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is neither necessary nor possible to exhaustively describe all embodiments here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. A PVC material, characterized in that, By weight, it includes the following components: 100 parts of PVC resin; 1-5 parts of modified graphene mixture; 5-15 parts filler; Processing aids 1-5 parts; Stabilizer 3-5 parts; Lubricant 0.3-1.1 parts; The modified graphene mixture is a mixture obtained by ball milling graphite powder, plasticizer, and quaternary ammonium salt surface treatment agent. The ball milling temperature is 65-90℃, the ball milling time is 20-30h, and the ball milling speed is 800-1000rpm / min; The weight ratio of plasticizer, quaternary ammonium salt surface treatment agent and graphite powder is (1~2):(0.4~0.8):1; The quaternary ammonium salt surface treatment agent is one or more of dodecyltrimethylammonium bromide, octadecyltrimethylammonium bromide, or glycidyltrimethylammonium chloride; The plasticizer is an aliphatic diester plasticizer.

2. The PVC material as described in claim 1, characterized in that, The ball milling temperature is 70~85℃.

3. The PVC material as described in claim 1, characterized in that, The filler is one or more of calcium carbonate, titanium dioxide, or pigment.

4. The PVC material as described in claim 1, characterized in that, The processing aid is one or more of the following: methyl methacrylate-acrylate copolymer, methyl methacrylate-styrene copolymer, methyl methacrylate-vinyl acetate copolymer, or acrylonitrile-styrene copolymer.

5. The PVC material as described in claim 1, characterized in that, The lubricant is one or more of polyethylene wax, oxidized polyethylene wax, stearic acid, or monoglyceride.

6. The PVC material as described in claim 1, characterized in that, The stabilizer is a calcium-zinc composite stabilizer.

7. A method for preparing the PVC material according to any one of claims 1 to 6, characterized in that, The process includes the following steps: graphite powder, plasticizer, and quaternary ammonium salt surface treatment agent are ball-milled to obtain a modified graphene mixture; the modified graphene mixture is mixed with the remaining components and stirred and heated until the temperature reaches 115~125℃, then stirred and cooled; and finally, when the temperature drops below 50℃, it is plasticized and extruded to obtain PVC material.

8. The use of the PVC material according to any one of claims 1 to 6 in the preparation of PVC pipes.

Citation Information

Patent Citations

  • Heat resistant polyamide compositions

    CN105283510A

  • High-gloss high-glass-fiber reinforced PA6 material and preparation method thereof

    CN115216141A